2015
DOI: 10.7567/jjap.54.04dh02
|View full text |Cite
|
Sign up to set email alerts
|

BaTiO3 based relaxor ferroelectric epitaxial thin-films for high-temperature operational capacitors

Abstract: The epitaxial growth of 0.6[BaTiO 3 ]-0.4[Bi(Mg 2/3 Nb 1/3 )O 3 ] (BT-BMN) relaxor ferroelectric thin-films on (100) Nb doped SrTiO 3 substrates has been achieved and the structure is investigated for high-temperature capacitor applications. The post growth annealing decreases the oxygen vacancy and other defects in BT-BMN films, resulting in the enhancement of dielectric constant. An insertion of intermediate SrRuO 3 layers as an electrode instead of Pt, sandwiching the film, is found to be more effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Organic electrolytes, dissolved in volatile organic solvents such as acetonitrile, are also limited to moderate operating temperatures. Ionic liquids, , ionogels, , polymer composites, perovskites, , and ceramic electrolytes have been the subject of recent investigations for electrolytes with increased thermal stability. Nevertheless, it has been found that many room temperature ionic liquids degrade at temperatures above 250 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Organic electrolytes, dissolved in volatile organic solvents such as acetonitrile, are also limited to moderate operating temperatures. Ionic liquids, , ionogels, , polymer composites, perovskites, , and ceramic electrolytes have been the subject of recent investigations for electrolytes with increased thermal stability. Nevertheless, it has been found that many room temperature ionic liquids degrade at temperatures above 250 °C .…”
Section: Introductionmentioning
confidence: 99%
“…These positions are symmetrical and consistent with the results reported in the literature. 33–35 There are other minor satellite peaks in addition to the above-mentioned peaks. The detailed characteristics of the satellite peaks are as follows.…”
Section: Resultsmentioning
confidence: 99%
“…where ε max , ε min , and ε RT are respectively the maximum, minimum and room temperature dielectric constants [53]. The optimum BFO25-BTO75 film shows a very high dielectric constant stability,…”
Section: Resultsmentioning
confidence: 99%